Meta Analysis Study : The Effect of HIIT Training on VO2max Improvement of Football Athletes - Yunus, Mocahmmad; Pratama, Muhammad Hamzah; Wahjuni, Endang Sri (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
Many studies have examined the effect of HIIT on the VO2max of a soccer athlete in sports. These various studies show that HIIT training has a positive effect on increasing an athlete's VO2max , but the results of each study tend to be different. Therefore, a comprehensive analysis is needed to provide precise and accurate information regarding the impact of HIIT training variations on an athlete's VO2max . This study focuses on testing the Effect Size of the effect of HIIT training variations on an athlete's VO2max in sports. The data from this study come from several studies that have been conducted and published on the Google Scholar database using the keywords: Influence; HIITs; VO2max ; Football. In the data analysis process, there are several steps, such as identifying variables, finding r values, converting r values into z distributions that reflect the effect size of each study, calculating variance, calculating the Standard Error of z, and performing summary effect calculations. Summary effect calculations were performed using the statistical program Jeffreys's Amazing Statistics Program (JASP). From the results of this study, it was concluded that there was a significant effect between HIIT training and an increase in VO2max in soccer athletes. The Random Effect Correlation (r_RE) has a value of 1.0602. Based on these findings, it can be concluded that the impact of HIIT training on increasing VO2max in soccer athletes is significant and has a high category.